JURISDICTION OVER LATROCÍNIO (ROBBERY RESULTING IN DEATH) LIES WITH THE BENCH, NOT WITH THE JURY (CIPEEX, 2025)
This paper analyzes jurisdiction for prosecuting and adjudicating latrocínio (robbery resulting in death) in Brazilian criminal law and explains why, despite the lethal outcome, it does not fall within the Jury’s remit. It is a doctrinal and case-law review that systematizes the legal nature of latrocínio as a property offense aggravated by result—rather than an intentional crime against life—and the consequences of that classification for determining the natural judge. The aim is to set out the normative grounds and judicial criteria that assign jurisdiction to a single-judge court, distinguishing it from the jury-trial procedure. The method consisted of examining scholarship, article 157(3)(II) of the Penal Code, and decisions that apply the amotio/apprehensio theory to the consummation of robbery, under which mere removal of the thing suffices without requiring peaceful possession; the possibility of attempt where the victim survives is also considered. The findings indicate that latrocínio is a complex offense (robbery plus homicide, with animus necandi) that predominantly protects property; therefore, the death result does not shift jurisdiction to the Jury. It concludes that improper submission to the Jury entails absolute lack of jurisdiction, nullifying the trial and requiring remand to the competent court, thereby preserving typological coherence and the natural-judge principle.